Sustainability Governance in Agribusiness SMEs: A Bibliometric Analysis - Qalbin Salim Fazli; Ghalieb Mutig Idroes; Mussa Isaack Delya; Erick Hironimus Kihwili; Jackson Bulili Machibya; Fazli Syam BZ (Indatu Journal of Management and Accounting, 2026)
The growing global emphasis on ESG practices, resilient food systems, and sustainable development has intensified scholarly attention toward sustainability-related governance in agri-food enterprises. This study examines the intellectual structure, thematic evolution, and research trends of sustainability governance research within agribusiness small and medium-sized enterprises (SMEs) through a comprehensive bibliometric analysis. Bibliographic data were retrieved from the Scopus database using a PRISMA-based screening procedure, resulting in 116 English-language journal articles published between 2005 and 2025. The analysis was conducted using VOSviewer and Biblioshiny to evaluate publication trends, collaboration networks, thematic structures, and influential publications. The findings reveal a substantial increase in scientific production after 2019, indicating growing academic interest in sustainable supply chains, resilience, digitalization, and governance-oriented business transformation. Thematic evolution analysis demonstrates a transition from conventional discussions on local food systems and operational sustainability toward more integrated themes involving circular economy, blockchain, ICT adoption, and adaptive resilience. The results further highlight the increasing role of technology-enabled governance mechanisms and interdisciplinary collaboration in strengthening sustainable agri-food ecosystems. However, geographical disparities and limited integration across sustainability dimensions remain evident, particularly in developing economies. This study contributes by positioning sustainability governance in agribusiness SMEs as an emerging interdisciplinary research domain and provides insights for future research and sustainable agri-food policy development.